(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two species of mealybugs have been found recently on the roots of Aloaceae. One of them was described originally as Ripersia speciosa De Lotto from the Democratic Republic of Congo on the roots of Coreopsis sp.(Compositae). lt now occurs under glass at the Royal Botanic Gardens, Kew, England, and at the Botanic Garden, Padua, Italy. The species possesses hind tibiae with unusual translucent pores and cannot be placed in any known genus. A new genus, Trochiscococcus gen. n., is described for it. Rhizoecus aloes sp. n. is also described from material collected under glass at the Royal Botanic Gardens, Kew, England.